Enhancing power, agility, and balance through core strength training among racquet athletes / Nur Dina Adriana Nor’Azman ... [et al.]. - Nor’Azman, Nur Dina Adriana; Linoby, Adam; Sazali, Razif; Md Yusoff, Yusandra; Haziq, Amrun; Mohd Nasir, Muhammad Zulqarnain (Universiti Teknologi MARA, Negeri Sembilan, 2025)
Core strength training is critical for enhancing athletic performance, yet its specific impact on power, agility, and balance among racquet players remains underexplored [1]. This study investigates these acute effects, addressing a gap in research, particularly for university-level badminton athletes. By understanding these relationships, the findings aim to guide targeted interventions for improved performance in racquet sports [2]. This study involved 20 badminton players (ages 18–29, ≥1 year experience) performing core strength exercises: mountain climb (40 sec), plank (1 min), bicycle crunch (15 reps), and medicine ball slams (10 reps), all in 3 sets. Power, agility, and balance were assessed using the standing broad jump, slalom test, and tandem walk test, respectively, to evaluate acute effects [3].